Pilot study: In vitro reduction of hemoglobin from canine blood with hemoperfusion using the Cytosorb® adsorber - Kathrin Spiegel; René Dörfelt; Katrin Hartmann; Florian Sänger (PLoS ONE, 2025)
Cell-free hemoglobin (cfHb) can be toxic and lead to kidney injury. This study assessed the in vitro reduction of cfHb from canine hemolyzed blood using hemoperfusion with a Cytosorb® cytokine adsorber. Canine whole blood was processed in linear and circular setups, with three runs each, at 100 mL/min. Hemolysis and osmolarity adjustments were performed with distilled water and hypertonic saline. Anticoagulation was optimized with heparin (10,000 IU/L). A median of 3.38 L of hemoglobin solution was processed in the linear setup. Samples were collected after the adsorber and from the waste bag. In the circular setup, a median of 2.09 L was processed, with samples taken before and after the adsorber. CfHb concentration was measured using the XT-2000iV® hematology analyzer (Sysmex). A control setup without an adsorber was run for 24 hours to assess cfHb stability. In the linear setup, cfHb concentration decreased by a median of 17.8% (14.7–26.8%), from 1.7 mmol/L to a minimum of 0.9 mmol/L, with 12.1 g (11.9–23.5 g) of cfHb removed. The median cfHb concentration after the adsorber displayed a logarithmic increase from 0.9 mmol/L (0.8–1.2 mmol/L) to 1.6 mmol/L (1.4–2.1 mmol/L). After processing 2.4 L, no further reduction occurred. In the circular setup, cfHb was reduced by a median of 41.3% (46.1–45.0%), representing 17.4 g (14.6–19.0 g) removed after 13.0 L (13.0–14.0 L). The reduction plateau was reached after 13 L. The hemoglobin reduction ratio in the circular setup at 3 L processed cfHb-solution was 25.0% (23.1–33.3%) and was not different from the linear setup (p = 0.400). The cfHb clearance decreased in both setups over time. CfHb concentration in the control setup was stable for 24 hours. Hemoperfusion with the Cytosorb® adsorber reduced cfHb in vitro from a canine blood solution.